The Role of Local Community Associations as Intermediaries: A Multiple Case Study in A Rural Area - Pratiwi Pratiwi (STI Policy and Management Journal, 2020)
Intermediary actors in rural areas are expected to stimulate not only economic growth but also social inclusion. The studies of innovation intermediaries in rural areas are under-researched. This study investigates the role, capabilities, and the outcome of the engagement of local community associations as intermediaries in different sectors such as agriculture, food processing, and tourism product. This study describes the way innovation promotes rural development. This research employs a multiple case study method and analyzes data triangulation. The interviews have indicated that intermediaries in different sectors need to play different roles due to their sector drivers, stakeholders, and challenges. This study also describes the outcome of the engagement of the intermediaries in increasing well-being, trust among stakeholders, and local people capability to innovate. Further, the study draws policy recommendations for the governments to enhance the skills and impact of the intermediaries, including collaborations, proposal competition, annual awards, organizational learning, training, and benchmarking.